2005
DOI: 10.1590/s0100-204x2005000600013
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade de dispersão de Trichogramma em tomateiro estaqueado

Abstract: Resumo -Estudou-se a capacidade de dispersão de Trichogramma pretiosum Riley em ovos de Anagasta kuehniella (Zeller), na cultura do tomateiro, em diferentes estágios fenológicos e sistemas de condução das plantas. A dispersão de T. pretiosum, 24 horas após a liberação, foi de 7,37 a 7,94 m. A área de dispersão foi de 120,20 a 138,72 m 2 . O parasitismo foi de 53,1% a 87,3%, e significativo de acordo com o estágio fenológico da cultura. A liberação dos parasitóides para o controle de Tuta absoluta (Meyrick) dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 8 publications
0
19
0
6
Order By: Relevance
“…This shows the importance of Trichogramma species in the natural biological control of agricultural and forest pests (Zanuncio et al 2009) and corroborates the reported severe mortality of E.eucerus by T. maxacalli (Oliveira et al 2000;Murta et al 2008). Trichogramma, a natural enemy, is broadly distributed, specialized, efficient and crucial for integrated management of this pest (Pratissoli et al 2005). The greater structural complexity and variety of food resources of native vegetation increases the diversity (Thies et al 2003), longevity and fertility of parasitoids in adjacent plantations (Oliveira et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This shows the importance of Trichogramma species in the natural biological control of agricultural and forest pests (Zanuncio et al 2009) and corroborates the reported severe mortality of E.eucerus by T. maxacalli (Oliveira et al 2000;Murta et al 2008). Trichogramma, a natural enemy, is broadly distributed, specialized, efficient and crucial for integrated management of this pest (Pratissoli et al 2005). The greater structural complexity and variety of food resources of native vegetation increases the diversity (Thies et al 2003), longevity and fertility of parasitoids in adjacent plantations (Oliveira et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Palavras Chave: controle biológico; lagarta do eucalipto; parasitismo; parasitoide de pupa Parasitoids are important natural enemies for the equilibrium of agroecosystems because they have high species and hosts diversity (Oliveira et al 2000;Pratissoli et al 2005). Palmistichus elaeisis Delvare & LaSalle (Hymenoptera: Eulophidae) parasitizes and develops in Lepidoptera pupae of the families Arctiidae , Bombycidae , Crambidae (Bittencourt & Berti-Filho 2004;Chichera et al 2012), Lymantriidae (Tavares et al 2011;Zaché et al 2012), Muscidae (Zaché et al 2013), Noctuidae (Bittencourt & Berti-Filho 2004;Andrade et al 2010;Pereira et al 2013), Nymphalidae (Tavares et al 2013a), Notodontidae (Zanuncio et al 2015), Papilionidae (Tavares et al 2013b), and Saturniidae ; it also develops in Coleoptera pupae of the family Tenebrionidae .…”
Section: Introductionmentioning
confidence: 99%
“…The high rates of parasitism and emergence of P. elaeisis on A. gemmatalis pupae after storage at 12 ºC, mainly until the sixth day, confirm that the conservation of hosts at low temperatures is useful for parasitoid production programs (Pratissoli et al, 2003;Milward-deAzevedo et al, 2004;Pratissoli et al, 2005;Zanuncio et al, 2008).…”
Section: Discussionmentioning
confidence: 91%